Methodological Procedure for Determining the Fatwa of the National Sharia Council (DSN) Indonesian Ulama Majelis (MUI) Concerning Islamic Economics and Finance - Rahmi, Nispan; Aseri, Akhmad Fauzi; Anshary, Abdul Hafiz; Monady, Hanief; Badrian, Badrian (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
Religious fatwas related to sharia economics and finance have great urgency and benefits for sharia economic and financial actors. The Qur'an and Hadith require detailed and analytical interpretation to explain the problems that arise, especially regarding zanni propositions. Fatwas issued by Islamic religious experts play an important role in responding to contemporary problems in accordance with social, scientific and technological developments. This research uses a normative legal approach with library research methods. This approach includes a study of the DSN-MUI Manhaj al-Ifta procedures and Manhaj al-Ifta which are the basis for determining fatwas related to sharia economic and financial issues. The DSN-MUI fatwa must comply with correct procedures and methodology (Al-Manhaj), avoid excessive (Ifrathi) and reckless (Tafrithi), and follow two main approaches: gradual (Tadriji) and voluntary (Tathawwu'i), and use a fiqh that provides solutions (Makharij Al-Fiqhiyyah). The principles of Manhaj Al-Ifta DSN-MUI include Taysir Al-Manhaj, Tafriq Al-Halal 'an Al-Haram, I'adat Al-Nazhar, and Tahqiq Al-Manath. Taysir Al-Manhaj emphasizes ease within the limits of legal rules, while Tafriq Al-Halal 'an Al-Haram separates the halal from the haram. I'adat Al-Nazhar revises the views of previous scholars which are no longer relevant, and Tahqiq Al-Manath emphasizes the analysis of the causes ('Illah) of law in a changing context. The DSN-MUI fatwa was made through Ijtihad Jama'i which involved various ulama and experts from various fields to ensure the honesty and truth of the fatwa. In this way, the DSN-MUI fatwa can meet the needs of sharia economic actors, provide solutions, and remain based on strong sharia.